Implementing and Addressing Challenges of LIMASTERS Integration in Early Childhood Education: A Case Study - Mastikawati, Mastikawati; Nazurty, Nazurty; Sofyan, Hendra; Yantoro, Yantoro (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to explore the implementation and challenges of integrating LIMASTERS (Literacy, Mathematics, Science, Technology, Engineering, and Arts) in early childhood education within the School Mover Program in Jambi City. The research responds to the growing demand for 21st-century learning integration at the preschool level and examines how practices align with the principles of the Independent Curriculum.Design/methods/approach – A qualitative case study design was applied. Data were collected through classroom observations, in-depth interviews with teachers and the principal, and document analysis of lesson plans and children’s work. Data were analyzed thematically using the Miles and Huberman model of data reduction, display, and conclusion drawing.Findings – The study shows that literacy, mathematics, and arts are consistently integrated into daily learning, while science, technology, and engineering remain less developed. Teachers conduct initial assessments to align activities with children’s needs and interests. Key challenges include limited facilities, insufficient time, and teacher competencies. These are partly mitigated through peer collaboration, self-initiated training, and phased implementation.Research implications/limitations – The findings are context-specific and do not address long-term child development outcomes. Nonetheless, they provide valuable insights for designing integrative curricula and teacher training policies in Indonesian ECE (Early Childhood Education).Practical implications – The study offers a practical model for LIMASTERS integration through child-centered exploratory activities that emphasize interactive experiments, scaffolding, and contextualized learning. Originality/value – This research contributes a holistic framework for balancing literacy and STEAM within early childhood classrooms in a local Indonesian context, highlighting the potential of exploratory and contextual learning to advance curriculum reform.Paper type Case study